Methodological approach for an integrated female-specific study of anxiety and smoking comorbidity - Farris, Samantha G.; Smith, Jacqueline E.; Steinberg, Dana R.; Altman, Brianna R.; Lambert-Messerlian, Geralyn M.; Dunsiger, Shira I.; Williams, David M.; Saladin, Michael E.; Abrantes, Ana M. (Frontiers in Psychiatry, 2023)
Two primary ovarian hormones that fluctuate across the female menstrual cycle—estradiol and progesterone—have been independently linked in separate literatures to nicotine reinforcement and anxiety psychopathology. We identify existing methodological limitations in these literatures, describe an example protocol that was developed to address such limitations, highlight case examples, and offer insights on the resulting advantages and challenges. This protocol was an observational, prospective, within-subjects study of female cigarette smokers who were followed over the course of a complete menstrual cycle. Non-treatment seeking, female cigarette smokers (N = 50), between the ages of 18–40 who have a normal menstrual cycle (25–35 days in length) were recruited from the community. Females with anxiety or mood psychopathology represented 38.0% of the sample. Salivary progesterone and estradiol were assessed each morning via at-home saliva collection methods. Self-reported within-day momentary ratings of anxiety and nicotine reinforcement were collected using ecological momentary assessment (EMA) via a mobile app. Protocol compliance was >85%. Within- and between-subjects heterogeneity was observed in the progesterone and estradiol, anxiety, and nicotine craving measures, especially in the context of anxiety psychopathology. We aimed to integrate the anxiety and nicotine dependence literatures and advance the empirical study of the role of ovarian hormones. This protocol reflects an intensive, yet feasible approach to collecting daily-level naturalistic data related to estradiol, progesterone, anxiety, and nicotine reinforcement.